The Socialization of the 2024 Kudus General Election Commissions Regional Election for Beginner Voters through the P5 Program at SMAN 2 Bae - Rozaq, Muhammad Abdul; Addiansyah, M. Nur Rofiq (ARISTO, 2024)
This research aims to provide a knowledge horizon regarding the importance of socialization in the Kudus religions election, as a form of providing understanding to novice voters and oriented towards increasing competent community participation. This research also reconstructs an understanding regarding the importance of the P5 program to equip students or novice voters to have a soul. democratic at school and in the community, and able to respond intensively to political dynamics in regional elections. This research focuses on the General Election Commission institution to look at its existence and main tasks and functions to provide political understanding for novice voters contextually in social society. The research approach is in the form of a qualitative approach, with observation, deskriptive, documentation, comparative, literature review, group discussion forums and tables as concrete forms of research validity. The results of the research show that understanding politics for beginner voters is very much needed as the main capital in determining candidate preferences by looking at track records, vision and mission and utilizing digital media as a comprehensive source of information, as well as instilling in the souls of students as beginner voters in a democratic context which is very necessary to face Holy Pilkada 2024, then in terms of socialization it is necessary to increase the participation of the community and first-time voters as evidenced by the percentage after the 2024  regional elections that voter participation is very high with a percentage of 86.57%.